Understanding the Nature of Eco‐Leadership: A Mixed Methods Study of Leadership in Community Organizations. (2nd September 2019) - Kaufman, Eric K.; Kennedy, Rachael E.; Cletzer, D. Adam
Abstract: The purpose of this study was to explore and explain eco‐leadership in practice, specifically among community groups in Virginia's New River Valley. This paper describes relationships between community groups' leadership style and other factors while also highlighting an intricate mixed method design that ultimately led to a deep, rich understanding of these relationships. There were five research objectives: (1) Characterize the community groups' leadership culture; (2) Assess each group's cohesiveness; (3) Assess the groups' community project involvement; (4) Determine if relationships exist between the variables; and (5) Highlight the role of mixed methods in the emergence of findings. The study has implications for carrying forward the concept of eco‐leadership in research and practice.